KEBIJAKAN BISNIS DALAM PENINGKATAN HASIL PANEN PETANI KOPI DI KABUPATEN BENER MERIAH - Risna Dewi; Rizki Ananda (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
The issue is a lack of care for the coffee plant, which makes it easier for diseases and pests to spread and results in low harvests. In order for the community to experience progress, independence, and welfare in a setting of lasting social justice, the community must be prepared, and institutions within the community must be strengthened. Knowing in advance what coffee farmers require will allow the extension agency to create a collaborative program with farmer organizations as part of the Agriculture Service's empowerment approach to boost coffee yields. Developing the skills of communities that grow coffee and are part of farmer organizations through training. It is essential to take proper care of the plant, use high-quality seeds, get enough organic and inorganic fertilizer, and apply pesticides to keep out pests in order to improve the output of high-quality coffee.